British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages 260 APRIL 30, 1938 REPORT OF COUNCIL SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL 62. The local authorities which have used their powers are, in many cases, pianning and rebuilding, re-equipping, and restating many of these transferred hospitals in an endeavour to bring them up to, or even beyond, the standard of the voluntary hospital. The hospitals thus transferred and administered under Public Health Acts (in Scotland under the Local Government (Scotland) Act, 1929) will be open not only to the poor but to all the inhabitants of the area. Under Section 16 of the Local Government Act local authorities are required, subject to the patient's capacity to pay, to charge the whole or part of the cost of maintenance and treatment; in Scotland, under Section 28 of the Local Government (Scotland) Act, 1929, local authorities are empowered to make this charge. Local authorities in both countries are, however, empowered to accept payment from contributory scheme funds in lieu of direct payment by the patient. 63. Hospital provision should be included in a comprehensive national medical service. Practical considerations have led the Association to share the opinion expressed by the Royal Commission on National Health Insurance of 1926 and by the Departmental Committee on Scottish Health Services, 1936, that the inclusion of hospital provision in an insurance service is not possible. Among these considerations are the coexistence of two hospital systems as yet not fully correlated; the special characters, historical, administrative, and scientific, of the voluntary hospital system; the inadequacy of hospital accommodation; and the existence of a large contributory scheme movement at present making payments to hospitals in respect of ten million people. It is, however, of first importance that the hospitals of the country, both voluntary and municipal, should work as one service, that voluntary and statutory authorities should devise efficient machinery for co-operation with each other and with non-institutional health services, and that the available hospital accommodation should be adequate. Some of the problems of hospital co-operation, accommodation, staffing, and administration are dealt with in Sections IV (6) and V of this report. IV. SOME SPECIAL PROBLEMS (a) A National Maternity Service 64. The problems of maternity and in particular maternal mortaiity have received a great deal of public and professional attention in recent years. The reports of the Departmental Committee on Maternal Mortality and Morbidity, of the Scientific Advisory Committee of the Department of Health for Scotland, of the Departmental Committee on Scottish Health Services, and of the British Medical Association, and the report of an investigation into maternal mortality, issued by the Ministry of Health in 1937, are among the more important contributions. 65. Local authorities with welfare functions have, in their own areas, exercised the powers delegated to them under the Maternity and Child Welfare Act, 1918, particularly in establishing ante-natal clinics and in providing institutional accommodation for maternity cases, with the result that almost one-half of the pregnant women of the country attend ante-natal clinics and almost one-quarter are confined in institutions. The General Medical Council has improved the training of medical students in obstetrics in consequence of the recommendations of the Departmental Committee on Maternal Mortality and Morbidity. By the Midwives Act, 1936, local authorities have been given the duty of establishing or securing the establishment of services of whole-time salaried midwives. Further, there have been established by local authorities lists of medical practitioners specially interested in obstetrics who will be available to afford medical aid to midwives in emergency. 66. Nevertheless, there has been no substantial change in the rate of maternal mortality and little progress towards the establishment of a complete maternity service. The main defect has been that, while each development deals with some aspect or phase of the problem, there has been no concerted effort to deal with the problem as a whole. In the view of the Association, what is needed in the interest of the mother is the establishment of a national maternity service based upon the principle of continuity of medical and nursing care throughout pregnancy, labour, and the puerperium. The present system, under which it is frequently the case that a woman receives her antenatal care at the hands of one practitioner, is confined by a midwife, and, in the event of an emergency arising, is then attended by a practitioner who is without previous personal knowledge of the woman's pregnancy, should be replaced by one in which every woman is, throughout pregnancy, labour, and puerperium, under the care of her doctor and midwife, aided when necessary by a specialist and institutional service. 67. The Departmental Committee on Scottish Health Services reports as follows: 1. The problem of maternal welfare calls for the provision of a comprehensive maternity service with the object of preserving the lives of parturient women, avoiding invalidism among mothers, and preventing the present wastage of infant life. 2. The maternity service should be based on the doctor and midwife acting in concert, supplemented by consultants and institutional facilities. 3. The need for continuous medical supervision by a general practitioner would be met by an arrangement linked up with our proposals for extension of general practitioner services. It should be part of the arrangements with the general practitioner under the maternity service that he should provide continuous ante-natal supervision and should be available for consultation at every stage of labour and the puerperium, and should report on the case to the local authority, the report to include the results of post-natal examination. 68. The Association agrees with the recommendations of the Departmental Committee on Scottish Health Services that the continuous medical care should be provided by the general practitioner. The birth of a child is not a mere mechanical event unrelated to the life-history of the mother, and the incident of pregnancy should not be the signal for the transference of a woman from the care of her general practitioner to that of another practitioner. An illness occurring before a confinement may have an important bearing on it, while subsequent and related disorders may in turn affect the general health of the mother. 69. There has been in recent years a considerable increase in the number of women seeking to be confined in institutions. This is sometimes used as an argument in favour of divorcing the general practitioner from midwifery and replacing him by an obstetric specialist. The removal of midwifery from the normal sphere of activities of the general practitioner is likely to damage the interests of the patient and to affect adversely the efficiency of the practitioner. Further, the experience in those urban areas in which the institutionalization of maternity has grown up does not justify its extension. In such towns there has been no corresponding decline in maternal mortality; indeed there is evidence that institutional confinement carries with it a greater danger of infection than domiciliary confinement. Taking the country as a whole, the general practitioner still bears a heavy responsibility for midwifery in that he is called in, or remains liable to be cailed in, to over 400,000 births a year. The serious defect of the present situation is that he is often called in for the first time when something has gone wrong. 70. Many of the adverse circumstances in this sphere of practice are not inherent, but can be mitigated or eradicated. Were general practitioners to be made responsible for the ante-natal care of midwives' cases they would be able during pregnancy to instil confidence into 292/847/1/60